Subsurface Structure Models Of Sumbawa Island And Flores Back Arc Thrust Based On Gravity Data - Suhayat Minardi; Ahmad Mudyanto; Hiden Hiden (Postgraduate, University of Mataram, 2021)
Based on the BMKG report on Wednesday, July 29, 2018, at 05.47 WIB, an earthquake with a magnitude of 6.4 SR occurred at the epicenter at a depth of 24 km and was 47 km northeast of the island of Lombok. They are allegedly originating from the Back Arc Thrust Flores, the interaction between the Indo-Australian Plate and the Eurasian plate. This study aims to analyze the subsurface structure of the island of Sumbawa and Flores sea based on the distribution of density values. The analysis was carried out by modeling the subsurface structure based on regional gravity field anomaly data. The data used is secondary data downloaded from the topex.ucsd.edu page 18,400 measuring points. Data processing consists of data correction, separation of anomalies, determination of the Second Vertical Derivative (SVD) value, and 3D and 2D inversion modeling. The data corrections performed are Bouguer correction and terrain correction to produce the total gravity anomaly value. Upward continuation is used to separate regional anomalies and residual anomalies. Analysis of the Second Vertical Derivative (SVD) value was carried out to identify rock contact positions and fault structures. The 3D inversion modeling is done by making a mesh model, and to get a 2D cross-section, six slices are used in the 3D model. The results of the 3D model and 2D cross-section, namely the island of Sumbawa to the Back Arc Thrust zone of Flores, consists of 3 main layers comprised of the upper crust with a density of 2.29 gr/cc - 2.63 gr/cc, the middle crust with a density of 2.64 gr/cc - 2.90 gr/cc, and the lower crust with a density of 2.91 gr/cc - 3.14 gr/cc, and based on the model and SVD value, it shows that the Flores back fault, the reverse fault type, starts at a depth of Â± 26 km